Sectoral Potential Analysis of West Pasaman Regency Period 2018 – 2022 - Juli Adevia; Tia Sofiani Napitupulu (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
This study aims to identify the conditions of economic sectors, challenges, and the potential of each sector for the economy in the West Pasaman Regency. The GRDP data from 2018 to 2022 were analyzed using Klassen Typology and Location Quotient (LQ) analysis. The study's findings indicate that the agricultural, forestry, and fisheries sectors significantly contribute to the West Pasaman Regency's economy. The results of the Klassen Typology analysis reveal that the agricultural, forestry, and fisheries sectors and the manufacturing industry sectors need to improve their performance to stimulate economic growth in West Pasaman Regency. These two sectors are also considered fundamental commodities, with an average LQ value of 1.83 for the agricultural sector and an average value of 1.58 for the manufacturing sector.